Web-Based Gym Membership System with Semi-Automated QRIS Verification Developed Through Agile-Scrum - Ragel Trisudarmo; Anisa Ramdhani; Dila Mardiyanti; Nabila Anggi Permatasari (Nusantara Journal of Artificial Intelligence and Information Systems, 2026)
Gym membership administration that depends on manual processes is correlated with elevated rates of recording inaccuracies, protracted payment verification periods of membership status. This study presents the development and evaluation of a web-based gym membership information system at TGW Gym, Indonesia, integrating semi-automated QRIS payment verification through the Agile-Scrum framework. The system was built using Laravel and MySQL across five iterative sprints, encompassing member registration, package selection, QRIS payment proof upload, administrator verification, and membership renewal modules. Functional validation used black-box testing across all modules with eight test scenarios spanning the package selection, payment, and renewal pages. Performance metrics were obtained through structured pre and post-implementation observation over 15 transaction cycles. Black-box testing confirmed that all functional requirements were satisfied. Following implementation, the task success rate reached 92%, error rates decreased from 15-20% to 3-5%, and verification time fell from 10-15 minutes to 2-5 minutes per transaction. The system usability scale score of 78 (Grade B, Good) confirmed acceptable usability. The novelty lies in combining admin payment verification, an expiry-aware renewal workflow, and a semi-automated QRIS flow within a single architecture, a combination not present in prior gym management systems.